Effect of correction of hindfoot valgus deformity on ankle joint pain relief in rheumatoid arthritis cases: A report of two cases - Makoto Hirao; Hideki Tsuboi; Shosuke Akita; Masato Matsushita; Shiro Ohshima; Yukihiko Saeki; Jun Hashimoto (SAGE Open Medical Case Reports, 2014)
We often see painful ankle joint destruction with painful hindfoot valgus deformity in rheumatoid arthritis. Our policy in such cases has been to first correct the hindfoot deformity in the subtalar joint with fusion, but then ankle joint pain has been observed. Two women with rheumatoid arthritis underwent correction and fusion surgery for hindfoot valgus deformity. They had been using wheelchairs because of severe pain in the ankle joint and hindfoot despite extensive medical treatment. After surgery, both patients complained of no pain in the hindfoot. Furthermore, dramatic pain reduction in the ankle joint was also observed especially in a case without ankle joint instability. Consequently, the patients could walk without any support. Correction of valgus hindfoot deformity contributes to centralizing the weight-bearing line in the ankle joint, leading to ankle joint pain relief. It appears possible to preserve the ankle joint without additional ankle surgery even in rheumatoid arthritis cases, if ankle is stable.